2017
DOI: 10.1159/000477251
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Surgical Methods in the Treatment of Upper Tibia Osteosarcoma and Prognostic Analysis

Abstract: Background: We aimed to explore the clinical effects and prognosis of different surgical methods in upper tibia osteosarcoma. Methods: Among 112 patients with proximal upper tibia osteosarcoma, 40 patients were treated with amputation, 20 patients were treated with massive osteoarticular allograft, and the remaining 52 cases were treated with tumor resection and artificial joint replacement. Results: Recurrence was observed in 2 cases (5%) in the amputation group, in 6 cases (30%) in the massive osteoarticular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…One hundred and seven articles were excluded based on the inclusion criteria, while 23 articles were excluded, as they studied the same patient population, estimated from the institution, number of patients and name of the authors. At last, 13 articles met the inclusion criteria and were eligible for analysis [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . Screening and selection details are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and seven articles were excluded based on the inclusion criteria, while 23 articles were excluded, as they studied the same patient population, estimated from the institution, number of patients and name of the authors. At last, 13 articles met the inclusion criteria and were eligible for analysis [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . Screening and selection details are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We included 12 studies [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [27] analyzing the 5-year overall survival rate in 2826 patients; 1943 patients were treated with LSS and 883 with amputation. The overall pooled analysis demonstrated that the odds of 5-year overall survival was almost 2-fold in patients treated with LSS than those treated with amputation but with substantial heterogeneity (OR: 1.99; 95% CI: 1.35–2.93; I 2 = 74%, p < 0.001) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the main clinical treatment of OS is mainly surgery, but in most cases, the tumor of patients diagnosed with OS has transferred to the lungs, which greatly reduces the effectiveness of treatment and affects the prognosis of patients. 3,5 Although the prognosis of some patients can be improved through radiotherapy and chemotherapy, long-term drugs can easily lead to drug resistance and tumor relapse, and lower the survival of patients for the long term. 6 Thus, it is a must to better understand the pathogenesis and molecular mechanism of OS, which will contribute to the clinical treatment and prognosis of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common primary malignant tumor of bone tissue, occurring mainly in adolescents and young adults. 1 Due to the characteristics of early metastasis and poor prognosis of OS, this aggressive malignant tumor has become a major cause of death-threatening adolescents and young adults. Although great progress in the diagnosis and treatment of OS in surgery, radiotherapy, chemotherapy and other aspects, the 5-year overall survival of OS patients has significantly improved to approximately 60-70%.…”
Section: Introductionmentioning
confidence: 99%